Effects of Vertical Molecular Stratifications and Microstructures on the Properties of Fullerene‐Free Organic Solar Cells. Issue 5 (18th January 2022) - Dela Peña, Top Archie; Ma, Ruijie; Sharma, Anirudh; Xing, Zengshan; Jin, Zijing; Wang, Jiannong; Baran, Derya; Weng, Lu-Tao; Yan, He; Wong, Kam Sing
Abstract : From the past years, the most commonly reported state‐of‐the‐art binary bulk heterojunction organic solar cells (OSCs) are mostly based on mixtures of polymer donors and fullerene‐free acceptors (polymer:NFA). However, along with it are a number of contradictory propositions, including (but not limited to) strategies to reduce energy loss and improve photocurrent generation through energy level alignments. Due to the resulting high similarity of molecular fragments from polymer:NFA heterojunctions, the effects of vertical molecular stratification are not yet well studied. Herein, the time‐of‐flight secondary ion mass spectrometry (ToF‐SIMS) molecular depth profiling reveals a vertical stratification in PM6:IT‐4Cl and illustrates how it can significantly influence the photovoltaic properties. The said inhomogeneity is also bound to introduce microstructure variations within device active layers. Consequently, it is systematically demonstrated how thin‐film microstructures can influence optoelectronic properties, wherein important metrics (e.g., energy losses and molecular energy offsets) are highly dependent. Thus, the understanding from this work provides foundations for more precise development of strategies to further advance OSC technology in future studies. Abstract : Polymer donors and non‐fullerene acceptors are currently at the forefront of organic solar cell development. However, in contrast to fullerene‐based systems, the molecular structure of nonfullerenes is quite similar to polymers, making the effects of vertical molecular stratification and microstructures being less understood. Consequently, herein, this work provides overviews that allow a more precise understanding of photovoltaic metrics and optoelectronic properties.